Reasoning and Reuse in Software Architecture Design: Practices in the Argentine Industry - Carignano, Maria Celeste (2013)
Over the last years, software architecture design has gained significant importance in both, industrial and research areas due to its relevance in the software system development process. In this context, special attention has been given to the documentation of architects’ reasoning during an architectural design, highlighting the advantages and disadvantages of this activity. This work intends to present a view of architects’ practices in the Argentine industry regarding reasoning documentation and its subsequent use and access.